High diversity of Rickettsia spp., Anaplasma spp., and Ehrlichia spp. in ticks from Yunnan Province, Southwest China - Lu, Miao; Tian, Junhua; Wang, Wen; Zhao, Hongqing; Jiang, Hai; Han, Jizhou; Guo, Wenping; Li, Kun (Frontiers in Microbiology, 2022)
Rickettsia, Anaplasma, and Ehrlichia belonging to the order Rickettsiales are causative agents of tick‐borne diseases in humans. During 2021, 434 ticks including Rhipicephalus microplus and R. haemaphysaloides were collected from three sampling sites in Yunnan Province, Southwest China, and analyzed for the presence of these bacteria. Nine bacterial species were identified, including two Rickettsia spp., three Anaplasma spp., and four Ehrlichia spp., some of which are potential human pathogens. Genetic and phylogenetic analysis on 16S rRNA, gltA, groEL, ompA, ompB, and sca4 genes indicated the presence of a novel spotted fever group Rickettsia (SFGR) named “Candidatus Rickettsia shennongii” in six of the 38 R. haemaphysaloides ticks from two locations, Dehong Autonomous Prefecture and Honghe City. Another SFGR species, Candidatus Rickettsia jingxinensis was detected in ticks from all three sites, with an overall positive rate of 62.67%. Three other human pathogenic species, Anaplasma ovis (1.38%, 6/434), Ehrlichia canis (16.36%, 71/434), and E. chaffeensis (0.23%, 1/434) were detected in these ticks and characterized. Moreover, Ehrlichia sp. (4.84%, 21/434), E. minasensis (7.37%, 32/434), A. marginale (6.91%, 30/434), and Cadidatus Anaplasma boleense (1.15%, 5/434) were detected in R. microplus ticks, for which pathogenicity to humans remains to be determined. The results reveal the remarkable diversity of Rickettsiales bacteria in ticks from Yunnan Province, Southwest China. The high infection rate of some human pathogenic bacteria in ticks may indicate potential infection risk in humans, and it highlights the need for surveillance in local populations.